PENGARUH SUKU BUNGA TERHADAP PENGAMBILAN KEPUTUSAN KREDIT BRIGUNA PADA PT BANK RAKYAT INDONESIA (Persero) Tbk KANTOR UNIT CITRA NIAGA SAMARINDA - Adi Suroso, Annisa Almukarramah, LCA. Robin Jonathan (EKONOMIA, 2016)
Based on the research that has examined the influental interest rates significantly to the credit decision making. To analyze and prove the Influence of Interest Rate Decision Decision Against Credit at PT Bank Rakyat Indonesia ( Persero ) Tbk Unit Office Citra Niaga Samarinda. This gives the sense that the low level of interest rates will make the customer interested in borrowing because of the burden of costs result from the interest charged by the Bri can still be accessible in revenue a days. So the decision taking effect on credit interest rate on PT Bank Rakyat Indonesia (Persero) Tbk Unit Citra Niaga of Samarinda.conclusion this study supports the results of the research. Most of the credit is determinated by taking the needs of the customer, but the interest rate is a highly influential in determining the credit is taken